2011
DOI: 10.1017/s0033291710002588
|View full text |Cite
|
Sign up to set email alerts
|

Emotional triggering and low socio-economic status as determinants of depression following acute coronary syndrome

Abstract: Background. The determinants of depression following acute coronary syndrome (ACS) are poorly understood. Triggering of ACS by emotional stress and low socio-economic status (SES) are predictors of adverse outcomes. We therefore investigated whether emotional triggering and low SES predict depression and anxiety following ACS.Method. This prospective observational clinical cohort study involved 298 patients with clinically verified ACS. Emotional stress was assessed for the 2 h before symptom onset and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
(71 reference statements)
2
15
0
Order By: Relevance
“…The women of the highest income class tended to become depressed more often, though only slightly, unlike the men, probably because the causes of depression relating to this variable are distinct between genders. 28 …”
Section: Discussionmentioning
confidence: 99%
“…The women of the highest income class tended to become depressed more often, though only slightly, unlike the men, probably because the causes of depression relating to this variable are distinct between genders. 28 …”
Section: Discussionmentioning
confidence: 99%
“…In a sample of 298 men and women low household income was associated with elevated depression symptoms at three weeks, six months and one year following ACS and this effect was independent of other demographic and clinical risk factors as well as history of depression [17]. In CABG samples, some investigators have used another marker of socioeconomic position, education, finding that low education is associated with greater risk of pre-operative depression [4,18], but others have not supported this effect [2].…”
Section: Introductionmentioning
confidence: 92%
“…The impact of stress on the development of depression after MI has not been studied extensively. One study of 314 MI patients found that stressful life events over the 12 months before MI was not associated with post-MI depression (20), whereas another showed that acute stress during the 2-hour trigger period before cardiac symptom onset predicted greater depression 1-12 months later, particularly among patients of lower socioeconomic status (104).…”
Section: Stress and Prognosis Following Myocardial Infarctionmentioning
confidence: 99%